Assessing Dynamic Soil Properties in Southern New England Forests within an Ecological Site Framework. Issue 5 (20th September 2018) - Paolucci, Andrew J.; Stolt, Mark H.
Abstract : Core Ideas: Coniferous and deciduous forests are two common states within a glaciofluvial upland ecological site. Upland soils with contrasting particle size showed similar ecological potential. Poorly drained and very poorly drained riparian ecosystems should be considered separate ecological sites. Ecological sites are a framework for documenting ecosystem conditions within a region but few have been developed for forested ecosystems. We developed ecological site concepts for southern New England glaciated forested upland and riparian benchmark soils with contrasting inherent properties. Within upland and riparian soils, we quantified the resistance or resilience of dynamic soil properties following specific management or disturbance. Although the upland soils had contrasting particle size classes, the vegetation composition, tree productivity, and soil organic C (SOC) pools were similar, suggesting that these soils have similar ecological potential. Coniferous and deciduous upland sites showed minimal differences. Selective harvest of 50% of overstory trees in the uplands decreased C addition from litter by 28% ( p = 0.036) but did not significantly impact O horizon thickness or SOC contents, suggesting that C pools in these soils are resilient to selective harvesting. Although poorly and very poorly drained riparian soils had similar stands of Acer rubrum L., very poorly drained soils had larger SOC pools and thicker O horizons, and Carex stricta Lam. and Symplocarpus foetidus (L.) Salisb. ex W.P.C.Barton dominated the understory. These differences suggest these riparian soils should be considered separate ecological sites. Simulated N enrichment of riparian soils significantly ( p = 0.006) increased root biomass but not CO2 respiration. Over time, N additions may increase C pools in riparian soils. Our studies suggest that ecological site concepts can be applied in southern New England forest ecosystems to establish a framework for understanding plant and soil responses to disturbance or management.